Doing Feminist Biblical Criticism in a Women's Studies Context - Milne, Pamela J. (Atlantis)

(untitled) (Mount Saint Vincent University, 2012)
Can academic feminist biblical studies courses have a valid place within women's studies? This article examines how such courses, once housed in a religious studies program, have been refocused to equip women's studies students with analytical skills and to serve major themes in a women's studies curriculum.